Analysis of Judicial Considerations in Deciding on the Seizure and Return of Evidence of Illegal Logging: (Case Study of Decision Number 54/Pid.B/LH/2017/PNTjt and Decision Number 27/Pid.B/LH/2024/PN Plj) - Meliyana; Ikhwan, Muhammad; Badri, Ainul (Lex Journal : Kajian Hukum dan Keadilan, 2025)
Illegal logging is one of the most prevalent environmental crimes occurring in Indonesia. One critical aspect in its legal enforcement is the seizure and return of evidence, particularly transport equipment used in the commission of the crime. This study aims to analyze the judges’ considerations in deciding on the seizure and return of transport equipment as evidence in illegal logging cases, as well as to understand the legal procedures based on applicable regulations. This research employs a normative juridical method with statutory, case, comparative, and conceptual approaches. The data used are secondary data, including court decisions Number 27/Pid.B/LH/2024/PN Plj and Number 54/Pid.B/LH/2017/PN Tjt, along with legal instruments such as Law Number 41 of 1999 concerning Forestry and Supreme Court Circular Number 1 of 2008. In case No. 54/Pid.B/LH/2017, the panel of judges referred to Article 78 paragraph (15) of Law No. 41 of 1999 concerning Forestry, which stipulates that means of transportation used in committing a crime can be confiscated by the state. Therefore, in this case, the means of transportation used by the defendant was seized by the state. Conversely, in case No. 27/Pid.B/LH/2024/PN Plj, the panel of judges adopted a different legal consideration. In its ruling, the court ruled that the means of transportation be returned to the defendant, arguing that the economic value of the means of transportation was disproportionate to the state’s losses, thus depriving the defendant of the confiscation of the means of transportation. This discrepancy raises questions about the certainty and fairness of the law in applying sanctions regarding the seizure of evidence.